Pebula: Local wisdom of the Buton people considering the prevention and enforcement of corruption - La Ode Abdul Munafi; Tasrifin Tahara; Andi Tenri; Dinna Dayana La Ode Malim (Department Anthropology, Faculty of Social and Political Sciences Hasanuddin University., 2020)
Pebula is a Buton's terminology to refer to acts of corruption. The act of pebula can be in the form of fraud or embezzlement of the state budget, bribes, as well as taking advantage of deception by abusing public office, authority, and power. In the social and state system in Buton, there is a wisdom that reflects the spirit of eradicating pebula. This spirit is manifest through several practices in the life of the community and state that functionally reflect prevention and action (law enforcement) of criminal acts pebula. This study was conducted with a qualitative approach using data collection techniques through the manuscript, library research, and in-depth interviews with informants. This article describes how the prevention and enforcement approach to “pebula” is practiced in the society and state life in Buton as an effort to actualize a clean and accountable governance.